The design of a multi-cell box in pure bending for minimum weight - Houghton, D.S.; Chan, A. S. L. (College of Aeronautics, 1957)
The optimum skin thickness, web thickness and web pitch to be used for a multi-cell box of given depth under a given bending load are obtained by two different methods, resulting in a graph where the optimum geometry is plotted against the structural index for a given material